Rashid Zaid Al-Kilani (1905 - 1965 A.D) his life and poetry - Al-Tawarah, Anwar Mohammad Hamad (Journal of Arabic Language Sciences and Literature, 2023)
This study deals with the biography of one of the Jordanian educational, cultural and intellectual figures, who had clear imprints in the modern history of Jordan, especially in the process of initiation and construction, Rashid Zaid Al-Kilani. The study also noted the role of Al-Kilani in collecting Jordanian folk literature with melody and words, and organized by Bedouin poetry, elegies and folk songs. The study reached several results, the most important of which are: that the teacher Rashid Zaid Al-Kilani was one of the first pioneers who contributed to the development of the educational and educational renaissance at the level of the country, and that he excelled with great ingenuity in the systems of songs and folk songs until his style became a school in which a large number of poets and songs composed popular.
Keywords: Rashid Zaid Al-Kilani; education; schools; poetry; folk songs